The Relationship Between Knowledge Of Iron (Fe) Tablet Consumption Practices And The Incidence Of Anemia Among Pregnant Women In The Working Area Of Telaga Dewa Community Health Center, Bengkulu City - Fatima Azarah; Asmariyah Asmariyah; Suriyati Suriyati; Linda Yulyani; Kurnia Dewiani (CV. AFDIFAL MAJU BERKAH, 2026)
Anemia in pregnant women remains a health issue that can have adverse effects on both the mother and the fetus. One preventive measure against anemia is the proper consumption of iron tablets; however, the success of this effort is influenced by the level of knowledge pregnant women have regarding the proper consumption of iron tablets. The research question of this study is whether there is a relationship between knowledge regarding the proper consumption of iron tablets and the incidence of anemia among pregnant women in the service area of the Telaga Dewa Community Health Center, Bengkulu City. This study aims to determine the relationship between knowledge regarding the proper consumption of iron tablets and the incidence of anemia in pregnant women. This study employed a quantitative method with a descriptive-analytical design using a cross-sectional approach. The study population consisted of 378 pregnant women, with a sample of 45 respondents selected using purposive sampling. Data were collected using a questionnaire and hemoglobin level tests, then analyzed univariately and bivariately using the chi-square test. The results showed that of the 18 respondents with good knowledge, 16 (88.9%) were not anemic and 2 (11.1%) were anemic. Of the 11 respondents with adequate knowledge, 4 respondents (36.4%) were not anemic and 7 respondents (63.6%) were anemic. Of the 16 respondents with poor knowledge, 4 respondents (25.0%) were not anemic and 12 respondents (75.0%) were anemic. Overall, 24 respondents (46.7%) were not anemic, and 21 respondents (53.3%) were anemic. The chi-square test yielded a p-value of 0.000 (p<0.05), indicating a significant association between knowledge of how to take iron tablets and the incidence of anemia in pregnant women.